Valutazione di alcuni parametri di epatotossicità di nevirapina ed efavirenz su oltre 700 pazienti trattati per infezione da HIV. Assenza di connessioni con il sesso femminile ed una conta di linfociti CD4+ elevata - Roberto Manfredi; Leonardo Calza (Microbiologia Medica, 2007)
Despite some recent reports which claimed the hypothesis of an increased hepatotoxicity of the antiretroviral drug nevirapine in female patients with a CD4+ lymphocyte count above 250 cells/μL (especially pregnant women), in our open-label comparison of 742 patients treated for the first time with either a nevirapine or an efavirenz-based HAART as completely naïve patients, experienced subjects, and patients on salvage antiretroviral therapy, we did not disclose any increased hepatotoxicity in nevirapine-treated subjects, in particular with regard to both gender (females versus males), and HIV-related immune deficiency (as represented by a CD4+ count above versus below 250 cells/μL).